Pengaruh Pendidikan Islam terhadap Peningkatan Kualitas Hidup Masyarakat - Naim, Muhammad Nasrul; Saputra, Beni Mustika; G, Gusmaneli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic education plays a crucial role in enhancing the overall quality of life within communities, encompassing not only spiritual and moral dimensions but also social, economic, and cultural aspects. This article aims to comprehensively examine the impact of Islamic education on improving community well-being by exploring various transformations resulting from the application of Islamic values in the educational process. Using a qualitative approach that combines literature review and case analysis, the study finds that Islamic education effectively shapes individuals with noble character, fosters social awareness, and strengthens solidarity among community members. Furthermore, Islamic education aids communities in adapting to modern challenges by developing spiritual and emotional intelligence. The integration of Islamic principles into daily life provides a strong ethical foundation, enabling communities to balance material needs with spiritual fulfillment. Collaboration among Islamic educational institutions, families, and communities is identified as a key factor in creating an environment conducive to the growth of quality individuals and groups. The findings indicate that Islamic education serves as an effective agent of social change, addressing social issues such as juvenile delinquency, poverty, and social conflicts, thereby contributing to the sustainable improvement of community welfare and quality of life. Therefore, strengthening Islamic education at all levels and improving the quality of educators is essential to support the development of a civilized, harmonious, and prosperous society.